(untitled) (World Bulletin of Public Health, 2024)
According to the International Diabetes Federation, there are 537 million people with diabetes in the world [1]. Patients with diabetes mellitus (DM) are at a significantly higher risk of developing complications of the underlying disease, including diabetic retinopathy (DR). Diabetic retinopathy is not only the most common complication of diabetes but it is also recognized as the most severe, as it often leads to irreversible vision loss. In 2021, there were 103 million people worldwide with some form of diabetic retinopathy, accounting for 22.3% of the total number of diabetic patients